Clinical response to interferon beta and glatiramer acetate in multiple sclerosis patients: a Brazilian cohort - Valéria Coelho Santa Rita Pereira; Fabíola Rachid Malfetano; Isabella D'Andrea Meira; Letícia Fêzer de Souza; Assuncion Martinez Liem; Angelo Maiolino; Soniza Vieira Alves-Leon (Arquivos de Neuro-Psiquiatria)
INTRODUCTION: Many patients with multiple sclerosis (MS) are currently receiving treatment with interferon beta (IFNb) and glatiramer acetate (GA). Identifying nonresponders patients is important to define therapy strategies. Several criteria for treatment response to IFNb and GA have been proposed. OBJECTIVE: It was to investigate the response to treatment with IFNb-1a, IFNb-1b and GA among relapsing-remitting multiple sclerosis (RRMS) patients. METHODS: We analyzed treatment response to IFNb and GA in ninety-one RRMS patients followed for at least one year. Clinical response was established by clinical criteria based on relapses, disability progression or both. RESULTS: We observed a proportion of nonresponders, ranging from 3.3 to 42.9%, depending on the stringency of the criteria used. CONCLUSIONS: Our sample of Brazilian patients with MS has similarities when compared to other studies and there was no statistically significant difference regarding age, gender, ethnicity or disease duration between responders and nonresponders.